Languages for Special Purposes an International Handbook - Budin, Gerhard; Humbley, John; Laurén, Christer (De Gruyter reference., 2018)
This handbook gives an overview of language for special purposes (LSP) in scientific, professional and other contexts, with particular focus on teaching and training. It provides insights into research paradigms, theories and methods while also highlighting the practical use of LSPs in concrete discourse situations. The volume is transdisciplinary oriented with a firm basis in the language sciences, including terminology, knowledge transfer, multilingual and cross-cultural exchange.